ANALYTICAL CALCULATION OF THE DEFORMATION STATE OF THE SAW GIN SAW TEETH BENDING UNDER THE ACTION OF A LOAD - Karimov, Nuriddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article developed a mathematical model of the technological process of heat treatment of saw teeth using a laser beam and recommended a modern and highly efficient technological process for processing saw teeth using a laser beam, which allows preserving the natural quality of products. As a result of the increased strength of the saw teeth using the new laser processing technology, the service life of saw blades has increased, the cost, productivity and efficiency of the saw cylinder has increased.